Interrater Reliability of Dynamic Muscle Testing After Breast Cancer Surgery in Women at High Risk of Lymphedema: To Improve Quality in Clinical Practice - Tina Korsholm-Rosfort BSc; Simone Larsen BSc; Thomas Aagaard MSc; Gunn Ammitzbøll MSc, PhD; Susanne O. Dalton MD, PhD (Integrative Cancer Therapies, 2020)
Background: The purpose of this study is to determine the interrater reliability of dynamic muscle tests in the early rehabilitation phase in women after breast cancer surgery with axillary lymph node dissection (ALND) based on the “preventive intervention against lymphedema after breast cancer” (LYCA) randomised controlled trial. Methods: Fifteen women treated with breast cancer surgery including ALND were recruited from participants in the LYCA trial. In this interrater reliability study, women were tested in 4 dynamic muscle tests by 2 physiotherapists at a Capital Hospital in Denmark. Intraclass correlation coefficients (ICCs) with 95% confidence intervals (CIs) was used to assess the relative reliability between raters. A Bland-Altman plot and limits of agreement were calculated to describe the absolute reliability. Results: All 6 subtests displayed high interrater reliability. ICC values were: leg press 0.96 (95% CI = 0.87-0.99), elbow flexion (contralateral) 0.94 (0.83-0.98), elbow flexion (affected arm) 0.93 (0.80-0.98), elbow extension 0.80 (0.41-0.93), shoulder abduction (contralateral) 0.89 (0.68-0.96), and shoulder abduction (affected arm) 0.91 (0.74-0.97). Cumulated interrater reliability for the test battery was very high (ICC = 0.99, 95% CI = 0.990-1.0). The absolute reliability of this study was considered high, and the absence of large shifts between mean and the line of 0 difference suggest no systematic bias that could influence clinical interpretation. Conclusions: The dynamic muscle tests evaluated in this study had high interrater reliability and can be used reliably in women in the postoperative phase after breast cancer surgery with ALND.